Grounding in English and Arabic news discourse - Khalil, Esam N. (Pragmatics & beyond, 2000)
Grounding in English and Arabic News Discourse explores the discourse notion of grounding (viz. the foreground-background structure), and examines it in the various structures that occur in short news texts. A text-level approach to grounding and the differentiation between several core concepts relating to the various textual and non-textual structures, distinguish the book from other approaches in the field. A corpus-based analysis focuses on sentence-initial expressions and examines the grounding-signalling function of several markers in both English and Arabic. The analysis captures constra.